2021
DOI: 10.1071/fp21233
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin improves the photosynthesis in

Abstract: This study investigated: (1) the effects of various concentrations of melatonin (MT) and Ca2+; and (2) the impact of crosstalk between these signal molecules on photosynthesis and salt tolerance of Dracocephalum kotschyi Boiss. Results indicated that 5mM CaCl2, as well as 100μM MT were the best concentrations for increasing shoot dry weight, leaf area, SPAD index, maximum quantum efficiency of photosystem II (Fv/Fm), and decreasing malondialdehyde content under salinity stress. The impact of MT on growth and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…MT induced the relative genes expression involved in Ca 2+ signaling in plants. 15 Meanwhile, combined MT and Ca 2+ treatment could promote photosynthesis and salt tolerance of Dracocephalum kotschyi, 16,17 improve postharvest quality of cassava, 12 and enhances resilience against arsenic toxicity of Vicia faba. 18 The only two studies showed that MT induced the synthetic of apigenin, luteolin, and rosmarinic acid in NaClstressed Dracocephalum kotschyi 19 and astaxanthin in Haematococcus pluvialis, 20 respectively, dependent on Ca 2+ /CaM signaling.…”
Section: Introductionmentioning
confidence: 99%
“…MT induced the relative genes expression involved in Ca 2+ signaling in plants. 15 Meanwhile, combined MT and Ca 2+ treatment could promote photosynthesis and salt tolerance of Dracocephalum kotschyi, 16,17 improve postharvest quality of cassava, 12 and enhances resilience against arsenic toxicity of Vicia faba. 18 The only two studies showed that MT induced the synthetic of apigenin, luteolin, and rosmarinic acid in NaClstressed Dracocephalum kotschyi 19 and astaxanthin in Haematococcus pluvialis, 20 respectively, dependent on Ca 2+ /CaM signaling.…”
Section: Introductionmentioning
confidence: 99%